Monte Carlo modelling of live-timed anticoincidence (LTAC) counting for Cu-64. (April 2018) - Bergeron, Denis E.; Fitzgerald, Ryan
Abstract: The radionuclide copper-64 is a promising candidate for nuclear medicine, but its complex decay creates challenges in the primary standardization of its activity. Monte Carlo simulations of live-timed anticoincidence (LTAC) counting of 64 Cu were used to calculate corrections to extrapolation intercepts, resulting in improved activity determinations. A small correction (−0.33%) to the linear extrapolation of LTAC data acquired with a γ-gate over the 1346 keV gamma peak was determined. We discuss the physical origin of the correction. We also use experimental data to demonstrate a Monte Carlo scaling that allows for inclusion of data acquired with a γ-gate set over the annihilation photon peak(s). Highlights: Monte Carlo simulations of 64 Cu LTAC found a 0.33% correction to the linear extrapolation. The intercept of a linear extrapolation is insensitive to some model deficiencies. A Monte Carlo scaling approach allows the use of data acquired with a γ-gate set over the annihilation photon peak(s).